Screening and Monitoring of Non-Communicable Diseases as an Effort to Implement Posbindu in Banjar Dukuh, Kesiman Petilan Village - Nuryanto, I Kadek; Dewi, Ni Nyoman Ari Kundari (Jurnal Abdimas ITEKES, 2021)
Non-communicable disease is a disease with a high incidence and increase every years. Non-communicable diseases often occur without symptoms and clinical signs so must beware. Insufficient awareness from the community regarding the early detection of non-communicable diseases must be immediately addressed, so that there is a need for efforts to implement Posbindu. The solution offered is by conducting community service activities in the form of screening and monitoring non-communicable diseases as an effort to implement Posbindu at Banjar Dukuh Desa Kesiman Petilan. The results of this activity are: (1) Implementation of counseling activities on non-communicable diseases, thereby increasing the knowledge of teachers at Banjar Dukuh Desa Kesiman Petilan about non- communicable diseases, (2) Implementation of Posbindu activities through checks to detect non-communicable diseases early can be a model for other Posbindu in early detection, monitoring, follow-up of non-communicable diseases and referral of non-communicable diseases.